KEPUASAN PENGUNJUNG TERHADAP AGROWISATA DI AGRIBISNIS ALOE VERA CENTER - Agustinus Bertolomeus Eko Dony Prayudi; Eva Dolorosa; Dewi Kurniati (Agric, 2019)
Aloe Vera is one of prime farming products in Pontianak so that the city government established Aloe Vera Center as the center for research and development of Aloe Vera product. In 2002, Aloe Vera Center also added an agritourism service there. Agritourism in Aloe Vera Center is expected to keep developing and face the challenge to attract visitors. For a unit of government under service sector, visitor is the most important parameter to make development planning. Therefore, as a basis of development planning, a research is needed to measure satisfaction variable in order to analyze visitors’ satisfaction. This study aims to determine the satisfaction variable of visitors who have the highest and lowest values and which variables are the main problems of visitors so that policy makers can use this research as a basis for planning development facilities, infrastructure and further service improvement. There are 100 respondents with the determination of samples from visitors who came. Conducted with non-probability sampling through convenience sampling method. There was a screening at the beginning of the questionnaire where the visitors who were used as respondents were visitors who had finished visiting. This research used Important Performance Analysis method and Customer Satisfaction Index. Research findings showed that from 5 dimensions and 27 variables analyzed, it was obtained that CSI score was 78,54%, which means that the satisfaction level of the visitors of Agribisnis Aloe Vera Center at whole is at the minimum limit, research finding is on the range 77%<X<80%. It means that, if there were no improvement on the attributes, the satisfaction of the visitors would also deteriorate. Besides, from Cartesian coordinate system, it was found that there were five prioritized variables that need to be improved. The researcher concluded that the Aloevera Manager must be giving attention to the parking area. More improving the cleanliness, comfort, neat location. Providing repairs to the Gazebo Facility and adding wudhu place, prayer mats and mukena as a prayer room facility. This needs to be done to increase customer satisfaction and increase visits. Managers must also make satisfaction analysis as a reference for preparing the following year’s budget.